Gasdermin D in pyroptosis - Brandon E. Burdette; Ashley N. Esparza; Hua Zhu; Shanzhi Wang (Elsevier, 2021)
Pyroptosis is the process of inflammatory cell death. The primary function of pyroptosis is to induce strong inflammatory responses that defend the host against microbe infection. Excessive pyroptosis, however, leads to several inflammatory diseases, including sepsis and autoimmune disorders. Pyroptosis can be canonical or noncanonical. Upon microbe infection, the canonical pathway responds to pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), while the noncanonical pathway responds to intracellular lipopolysaccharides (LPS) of Gram-negative bacteria. The last step of pyroptosis requires the cleavage of gasdermin D (GsdmD) at D275 (numbering after human GSDMD) into N- and C-termini by caspase 1 in the canonical pathway and caspase 4/5/11 (caspase 4/5 in humans, caspase 11 in mice) in the noncanonical pathway. Upon cleavage, the N-terminus of GsdmD (GsdmD-N) forms a transmembrane pore that releases cytokines such as IL-1β and IL-18 and disturbs the regulation of ions and water, eventually resulting in strong inflammation and cell death. Since GsdmD is the effector of pyroptosis, promising inhibitors of GsdmD have been developed for inflammatory diseases. This review will focus on the roles of GsdmD during pyroptosis and in diseases.